2022
DOI: 10.1002/ejoc.202200708
|View full text |Cite
|
Sign up to set email alerts
|

Stereoconvergent Synthesis of Cyclopentenyl Nucleosides by Palladium‐Assisted Allylic Reaction

Abstract: Dedicated to Professor Giovanni Palumbo for having inspired our passion for research and organic synthesis.The Tsuji-Trost reaction of cyclopentenyl carbonates was explored by experimental studies and computational calculations, in search for the synthetic conditions enabling the stereoconvergent synthesis of cyclopentenyl nucleosides. Under common conditions, cyclopentenyl reagents provide Tsuji-Trost products only in a weakly stereoconvergent manner. However, changes in the amount of catalyst (up to 1 eq) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Overall, these findings suggest that iminosugars represent attractive drug candidates for the treatment of Sanfilippo disease and therefore further efforts should be devoted to identify novel iminosugars effective in reducing HS and lysosomal accumulation in Sanfilippo patients. In the frame of our previous studies on the role of chirality in the pharmacological activity of iminosugars and other bioactive compounds, we recently highlighted the promising potential of unnatural l - gluco -configured iminosugars for the treatment of rare diseases. Particularly, l -NBDNJ ( ent - 2 , Figure ), the synthetic enantiomer of d -NBDNJ ( 2 ), showed an interesting potential for the treatment of Pompe lysosomal disease, while not acting as an inhibitor of the most common glycosidases, differently from its enantiomer .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these findings suggest that iminosugars represent attractive drug candidates for the treatment of Sanfilippo disease and therefore further efforts should be devoted to identify novel iminosugars effective in reducing HS and lysosomal accumulation in Sanfilippo patients. In the frame of our previous studies on the role of chirality in the pharmacological activity of iminosugars and other bioactive compounds, we recently highlighted the promising potential of unnatural l - gluco -configured iminosugars for the treatment of rare diseases. Particularly, l -NBDNJ ( ent - 2 , Figure ), the synthetic enantiomer of d -NBDNJ ( 2 ), showed an interesting potential for the treatment of Pompe lysosomal disease, while not acting as an inhibitor of the most common glycosidases, differently from its enantiomer .…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the example of d -NBDNJ, other iminosugars have been evaluated for application in CF . In the frame of our studies aimed to explore the pharmacological properties of biomimetic compounds, we highlighted the role of sugar chirality , on the anti-inflammatory and antibacterial properties of iminosugars. Particularly, our studies revealed the ability of unnatural l - gluco -configured N -alkyl-deoxyiminosugars to act as NLGase inhibitors, although less efficiently than their d -enantiomers and to strongly reduce the inflammatory response induced by P.…”
mentioning
confidence: 99%